THE EFFECTIVENESS OF GROUP COUNSELING WITH SELF-REFLECTION TECHNIQUES TO REDUCE SELFISH ATTITUDES IN STUDENTS AT BOARDING SCHOOL SMP PLUS JABAL RAHMAH MULIA MEDAN - Sasqia Salsa Zahra Nasution; Ira Suryani (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to determine the effectiveness of group counseling using the Muhasabah Diri technique in helping to reduce selfish attitudes among students at the Boarding School SMP Plus Jabal Rahmah Mulia Medan. The research used a quantitative approach with a pre-experimental method employing a one-group pretest-posttest design. The study population consisted of 51 ninth-grade students, with a sample of 6 students identified as having a high level of selfishness. The sampling technique used was purposive sampling, and data analysis was conducted using the Wilcoxon Signed Rank Test through the SPSS 22 for Windows application. Based on the statistical analysis, the obtained Z value was -2.201 with a significance value (Asymp. Sig. 2-tailed) of 0.028 < 0.05. These results indicate that group counseling using the Muhasabah Diri technique is effective in reducing selfish attitudes among students at the Boarding School SMP Plus Jabal Rahmah Mulia Medan.